Magnetic resonance imaging in HTLV-I associated myelopathy - Aílton Melo; Luciana Moura; Solana Rios; Marcos Machado; Gersonita Costa (Arquivos de Neuro-Psiquiatria, 1993)
Magnetic resonance imaging of the brain and spinal cord were carried out for seventeen consecutive patients with HTLV-1 associated myelopathy (HAM). Eight patients had brain abnormalities and four had decreased thoracic spinal cord diameter. Brain lesions were mostly located in subcortical and periventricular areas. Our data suggest that diffuse central nervous system lesions are present in patients with HAM.